Effective Factors in Corporate Environmental Responsiveness of Agricultural Production Cooperatives in Ilam Province - HOSSEN MEHDI ZADE; کامران طاهرپور; Zohreh Motamedi Nia (تعاون و کشاورزی, 2017)
Corporate environmental responsiveness (CER) refers to the extent to which organizations respond to natural environmental issues. The goal of this research was to investigate effective factors in CER of agricultural production cooperatives in Ilam Province, Iran. This was an applied research in terms of goal orientation and a descriptive-correlational study based on the method. The study population included 70 managers of agricultural production cooperatives in Ilam province. Census sampling method was applied in the study. For data collection, we used a closed-ended questionnaire. The face and content validity of the questionnaire were assessed by a panel of experts. Cronbach’s alpha was calculated to estimate the reliability of the questionnaire (85%). The findings revealed that the mean CER was below average. Based on the analysis of the questionnaire items, corporate policies were based on waste removal had the highest priority. On the other hand, corporate policies were based on the use of recycled raw materials and natural environmental training/seminars were utilized for corporate employees and managers were ranked the lowest among CER items.